2010
DOI: 10.1128/cmr.00034-09
|View full text |Cite
|
Sign up to set email alerts
|

Rifampin Combination Therapy for Nonmycobacterial Infections

Abstract: SUMMARY The increasing emergence of antimicrobial-resistant organisms, especially methicillin-resistant Staphylococcus aureus (MRSA), has resulted in the increased use of rifampin combination therapy. The data supporting rifampin combination therapy in nonmycobacterial infections are limited by a lack of significantly controlled clinical studies. Therefore, its current use is based upon in vitro or in vivo data or retrospective case series, all with major limitations. A p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
165
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(173 citation statements)
references
References 275 publications
5
165
2
1
Order By: Relevance
“…The combination of rifampicin plus trimethoprim/sulfamethoxazole is a theoretically even more attractive regimen for the treatment of MRSA infections for a number of reasons, including enhanced and intracellular antistaphylococcal activity, excellent bioavailability and favourable pharmacodynamics. 22,23 The combination is widely used in several European countries, especially for osteoarticular infections, although published evidence supporting its use remains sparse. 24,25 Moreover, since these antibiotics are available as generic agents, they offer substantial cost advantages over other agents such as linezolid and daptomycin.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of rifampicin plus trimethoprim/sulfamethoxazole is a theoretically even more attractive regimen for the treatment of MRSA infections for a number of reasons, including enhanced and intracellular antistaphylococcal activity, excellent bioavailability and favourable pharmacodynamics. 22,23 The combination is widely used in several European countries, especially for osteoarticular infections, although published evidence supporting its use remains sparse. 24,25 Moreover, since these antibiotics are available as generic agents, they offer substantial cost advantages over other agents such as linezolid and daptomycin.…”
Section: Discussionmentioning
confidence: 99%
“…Drug synergy has been demonstrated to result in more-efficient clearance of infections and to achieve clearance at lower drug concentrations (6). Examples of such cases include fusidic acid and rifampin for the treatment of methicillin-resistant Staphylococcus aureus infections and trimethoprim and sulfamethoxazole for the treatment of otitis media (7,8). Furthermore, recent theoretical work indicates that synergistic drugs can prevent treatment failure even when bacteria resistant to one of the drugs are present at the beginning of therapy (9).…”
mentioning
confidence: 99%
“…Staphylococcus aureus could easily invade professional phagocytes and persists in the acidic lysosome compartment for several days (Imbuluzqueta et al, 2010). Rifapentine and rifampin, which show enforced bactericidal activity in acidic conditions, have been applied extensively in combinational antimicrobial therapies against intracellular S. aureus infections (Forrest & Tamura, 2010). The in vitro infection experiments in the current study demonstrated that the incorporation of RPT into heLDL led to a significant reduction of intramacrophage S. aureus.…”
Section: Discussionmentioning
confidence: 68%